Frequency Monitoring and Control during Power System Restoration Based on Wide Area Measurement System - Saber Nourizadeh (Mathematical Problems in Engineering, 2011)
Frequency control during power system restoration has not been strongly addressed. Operators are often concerned with the offline sizing of load and generation steps, but, nowadays, the introduction of Wide Area Measurement System (WAMS) makes it possible to monitor the stability of power system online. The constraints of WAMS operation result in some changes in power system frequency control. This paper proposes a novel methodology for frequency control and monitoring during the early steps of power system restoration based on WAMS. Detailed load modeling is achieved based on the static load modeling approach. Power generators' modeling is also accomplished utilizing the single machine equivalent of the power system based on PMU measurements. Simulation results of the presented methodology on the 39 bus New England power system clearly show the effectiveness and applicability of the proposed method. The simulation results show that the presented approach has a completely acceptable precision and an outstanding speed with less than 0.05% error. The outstanding speed of the presented approach along with the result precision will result in a great promotion in power system restoration methodologies.